Clinical and manometric evaluation of women with chronic anal fissure before and after internal subcutaneous lateral sphincterotomy - Silvana Marques e Silva; Viviane Fernandes Rosa; Romulo Medeiros de Almeida; Marcelo de Melo Andrade Coura; Paulo Gonçalves de Oliveira; João Batista de Sousa (Journal of Coloproctology, 2012)
OBJECTIVE: To evaluate clinical and manometric parameters of chronic anal fissure females undergoing lateral internal sphincterotomy (LIS). METHODS: A total of eight women with chronic anal fissure who underwent LIS were included in this study. The preoperative assessment was performed one week before surgery and included general and anorectal examination, anorectal manometry, and Jorge Wexner questionnaire. The post operative follow up was made every 15 days until complete healing. Jorge Wexner questionnaires and anorectal manometry were repeated at 1 month and 3 months after the surgery. Time to healing, manometric changes and complications were assessed. RESULTS: All patients had preoperative increased anal resting pressure. The resting pressures and anal canal length were significantly decreased 3 months after surgery. Patients' complaints of itching and bleeding were also reduced. Fissures healed in 7 patients and median healing time was 45 days. No complications were observed due to the procedure. One patient had transient incontinence to flatus. CONCLUSION: Lateral internal sphincterotomy provided clinical improvement and reduced resting pressure of the internal anal sphincter in women with chronic anal fissure. OBJETIVO: Avaliar a evolução clínica e manométrica de mulheres com fissura anal crônica submetidas à esfincterotomia lateral interna subcutânea. MÉTODOS: Estudo prospectivo com oito pacientes. A avaliação inicial foi realizada por meio de questionários, exame físico e manometria anorretal na semana anterior ao procedimento cirúrgico. Durante o período pós-operatório, as pacientes foram avaliadas clinicamente a cada 15 dias, até a cicatrização completa. Os questionários e a manometria anorretal foram repetidos 1 mês e 3 meses após a operação. Foi avaliado o tempo para cicatrização da fissura, as alterações manométricas e as complicações decorrentes do procedimento. RESULTADOS: Todas as pacientes apresentavam hipertonia esfincteriana interna no período pré-operatório. Após 3 meses da operação, as pressões de repouso e o comprimento do canal anal funcional diminuíram de modo estatisticamente significante. Houve redução das queixas de prurido e sangramento. A cicatrização completa da fissura ocorreu em sete pacientes. A mediana do tempo de cicatrização foi de 45 dias. Não houve complicações decorrentes do procedimento. Uma paciente apresentou incontinência transitória para flatos. CONCLUSÕES: A esfincterotomia lateral interna subcutânea proporcionou melhora clínica e diminuição das pressões de repouso dos esfíncteres anais em mulheres com fissura anal crônica.